Comparação antropométrica, composição corporal, somatotipo e saltos verticais de atletas de voleibol de praia masculino - Batista, Gilmário Ricarte (2008)
The kinanthropometric characteristics are used by the sports science as selection criteria and detection of talents. Hence, this study aimed at comparing the anthropometrical profile, the body composition, the somatotype and the vertical jumps of the beach volleyball players. This study consists of 79 male beach volleyball players, being forty nine (n=49) Brazilian participants of the National Circuit and thirty (n=30) of 15 countries participating in the XV Pan American Games. In order to analyze the vertical jumps of the Brazilian the participants were allocated into two groups (G1 and G2) in agreement with the national ranking of their teams. The vertical jump protocol developed by Smith and collaborators was used to evaluate the vertical jumps of spike and block. The Heath-Carter anthropometrical technique (1990) was used for calculating the somatotype. The Student s t test with the Bonferroni adjustment was used to calculate the differences among the investigated variables. The multiple regression analysis was used to identify the contributions of the anthropometrical variables in the performance of the vertical jumps and the multivariance analysis was used to calculate the differences among the components of the somatotype. The Brazilian athletes of G1 were better than G2 in the spike jump (p <0.01), block jump (p <0.01) and in the block difference (p <0.01). The prediction model of the spike jump of G2 included the body mass and standing spike reach (adjusted R2 = 0.77), the body mass and the standing block reach were also included in the model of the block jump (adjusted R2 = 0.73). The regression model of G1 was not statistically significant. As for the somatotype, statistically significant differences were found between the Brazilians and the Pan Americans (Wilks' lambda = 0.498; p <0.05). The Brazilian somatotype was classified as balanced mesomorph (2.7-4.3-3.0) and the Pan American somatotype as endomorphic mesomorph (3.5-4.6-2.4). As to the specific position of the block game (2.8-4.3-2.9) and the defense game (2.6-4.4-3.0), the Brazilian somatotype was classified as balanced mesomorph and the Pan American somatotype, the block (3.7-4.4-2.4) and the defense (3.4-4.9-2.3), was classified as endomorphic mesomorph. In conclusion, the vertical jump height (spike and block) influences the male Brazilian beach volleyball players performance. The physical type of the Brazilian blockers and defenders was similar with relationship to the somatotype. The Brazilian and Pan American beach volleyball players differ in terms of kinanthropometric characteristics. This work had a multidisciplinary feature with the participation of several departments and laboratories, like the Physiotherapy Department, the Nutrition Department, the Physical Education Laboratory, thus corroborating the multidisciplinary research feature